Realization of regional operational programme of the Opolskie Voivodeship. Assumption and activities in the Opole Agglomeration in the context of sustainable development - Dembicka-Niemiec, Agnieszka (Realizacja założeń RPO WO 2014-2020 oraz inwestycji w aglomeracji opolskiej w kontekście zrównoważonego rozwoju, 2019)
The objective of the article is the identification and assessment of measures contributing to the development of the Opole Agglomeration in the context of the concept of sustainable development. It identifies the measures undertaken in the scope of the conducted policy within the existing functional area, and evaluates them in the context of the assumptions of sustainable development. The implementation of such an objective also involved the determination of the types of projects financed within the Regional Operational Programme of the Opolskie Voivodeship 2014-2020 (ROP OV 2014-2020), and the scope of their influence. The analysis was based on three main aspects of sustainable development: economic, social, and environmental. Moreover, the study attempts the identification of the benefits from the measures and policy concerning the said area implemented by the Opole Agglomeration Association. The study was based on the desk research method involving the analysis of strategic and programming documents and statistical data
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 32-46
Keywords: Opole Agglomeration; sustainable development; functional area; aglomeracja opolska; zrównoważony rozwój; obszar funkcjonalny